About causes of sepsis in pemphigus foliaceus - Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
I have come across a letter to the Editor recently published in the “Advances of Dermatology and Allergology” titled: Pemphigus foliaceus complicated by sepsis of the aetiology of Yersinia enterocolitica after eating cheesecake (Adv Dermatol Allergol 2020; XXXVII (1): 111–113; DOI: https://doi.org/10.5114/ada.2018.78880).